Cardiovascular Imaging Techniques in Systemic Rheumatic Diseases - Atzeni, Fabiola; Corda, Marco; Gianturco, Luigi; Porcu, Maurizio; Sarzi-Puttini, Piercarlo; Turiel, Maurizio (Frontiers in Medicine, 2018)
Patients with by systemic rheumatic diseases (SRDs) are at significantly greater risk of cardiovascular (CV) risk factors, CV events, and mortality than the general population. Although CV involvement in such patients is highly heterogeneous and may affect various structures of the heart, it can now be diagnosed earlier and promptly treated. The examinations used include transthoracic or transesophageal echocardiography, magnetic resonance imaging (MRI), and computed tomography (CT) to investigate valve abnormalities, pericardial disease and ventricular wall motion defects. Coronary arteries can be investigated invasively using quantitative coronarography or intravascular ultrasound (IVUS) to assess coronary diameter, or non-invasively using transthoracic or transesophageal ultrasonography (US), MRI, positron emission tomography (PET) after endothelium-dependent vasodilatory provocation, or CT to assess coronary flow reserve. Finally, peripheral circulation can be measured invasively by means of the strain-gauge plethysmography of an arm after the intra-arterial infusion of an endothelium-dependent vasodilator and/or non-invasively by means of US or MRI measurements of flow-mediated vasodilation of the brachial artery. CV imaging is reliable in screening, diagnosing and following up CV involvement, but new technologies such as speckle tracking echocardiography and/or 3-dimensional US are more accurate diagnostically.